Kualitas Soal Pilihan Ganda Kelas VI Tema 1 MI MHM Banjarsari Ngronggot Nganjuk - Liana Mutholiin; Bustanul Arifin (Institut Agama Islam Tribakti Kediri, 2021)
This research was conducted to find out how to compile and analyze the Odd End Semester Assessment questions at MI MHM Banjarsari, and to determine the quality of the multiple choice items of the Odd End Semester Assessment Grade VI Theme 1 MI MHM Banjarsari Academic Year 2019/2020. The research design used in the analysis of the quality of the multiple choice items Final Assessment of the odd semester class VI Theme 1 MI MHM Banjarsari Academic Year 2019/2020 is quantitative descriptive. Data collection in this study used document analysis method. The source of the data of this study was the question sheets and answer sheets of students participating in the Odd End Semester Assessment (PAS) of Class VI Theme 1 MI MHM Banjarsari. Calculation of the level of difficulty, different power, the effectiveness of deceit, the validity and reliability of the instrument in this study using the Anates V 0.4 program. The results of the research that have been done show that the quality of the final semester semester 1 question items in MI MHM Banjarsari in 2019/2020 from a total of 35 multiple choice questions viewed from the difficulty level obtained as many as 10 items (28.57%) with the difficulty level of questions in very easy category, 7 items (20%) in the easy category, 14 items (40%) in the medium category, 3 items (8.57%) in the difficult category, and 1 item (2.86%) in the very difficult category. Judging from the different power of the final semester assessment questions, theme 1 found 5 items (14.29%) in the very bad category, 13 items (37.14%) in the bad category, 6 items (17.14%) in the category enough, 10 items (28.57%) in the good category, and 1 item (2.86%) in the very good category. Judging from the deception of answers to the odd semester final assessment questions, there were 3 questions (8.57% in the very bad category, 6 questions (17.14%) in the bad category, 4 questions (11.48%) in the good category, and 22 questions (62.86%) in the very good category Judging from the validity of the odd semester final evaluation questions theme 1 obtained valid questions (significant / very significant) of 15 questions (42.86%) and for invalid questions a total of 20 questions (57.14%) In terms of reliability, it was obtained 0.81. Thus it can be concluded that the quality of the items can be said to be less good. [Penelitian ini dilakukan untuk mengetahui cara menyusun dan menganalisis soal Penilaian Akhir Semester ganjil di MI MHM Banjarsari, dan untuk mengetahui kualitas butir soal pilihan ganda Penilaan Akhir Semester ganjil kelas VI Tema 1 MI MHM Banjarsari Tahun Ajaran 2019/2020. Desain penelitian yang digunakan dalam analisis kualitas butir soal pilihan ganda Penilaan Akhir Semester ganjil kelas VI Tema 1 MI MHM Banjarsari Tahun Ajaran 2019/2020 adalah deskriptif kuantitatif. Pengumpulan data dalam penelitian ini menggunakan metodeanalisis dokumen. Sumber data penelitian ini adalah lembar soal dan lembarjawaban siswa peserta Penilaian Akhir Semester (PAS) ganjil Kelas VI Tema 1 MI MHM Banjarsari. Penghitungan tingkat kesulitan, daya beda, efektivitas pengecoh, validitas dan reliabilitas instrumen pada penelitian ini menggunakan program Anates V 0.4. Hasil penelitian yang telah dilakukan menunjukan bahwa kualitas butir soal penilaian akhir semester ganjil tema 1 di MI MHM Banjarsari tahun 2019/2020 dari total 35 soal pilihan ganda ditinjau dari tingkat kesukaran didapatkan sebanyak 10 butir soal (28,57%) dengan tingkat kesukaran soal dalam kategori sangat mudah, 7 butir soal (20%) dalam kategori mudah, 14 butir soal (40%) dalam kategori sedang, 3 butir soal (8,57%) dalam kategori sukar, dan 1 butir soal (2,86%) dalam kategori sangat sukar. Ditinjau dari daya beda soal penilaian akhir semester ganjil tema 1 didapatkan 5 butir soal (14,29%) dalam kategori sangat jelek, 13 butir soal (37,14%) dalam kategori jelek, 6 butir soal (17,14%) dalam kategori cukup, 10 butir soal (28,57%) dalam kategori baik, dan 1 butir soal (2,86%) dalam kategori sangat baik. Ditinjau dari pengecoh jawaban soal penilaian akhir semester ganjil tema 1 terdapat sebanyak 3 soal (8,57% dalam kategori sangat buruk, 6 soal (17,14%) dalam kategori buruk, 4 soal (11,48%) dalam kategori baik, dan 22 soal (62,86%) dalam kategori sangat baik. Ditinjau dari validitas soal penilaian akhir semester ganjil tema 1 didapatkan soal valid (signifikan/sangat signifikan) sejumlah 15 soal (42,86%) dan untuk soal yang tidak valid sejumlah 20 soal (57,14 %). Ditinjau dari reabilitas didapatkan sebesar 0.81. Dengan demikian dapat disimpulkan bahwa kualitas butir soal bisa dikatakan kurang baik]